A new strategy for cellulases application in high temperature industrial scenarios with syringic acid assisting - Qiuping Ran; Mengtian Huang; Huanan Li; Bixin Chen; Lili He; Xinxin Cui; Jiashu Liu; Zhengbing Jiang (GCB Bioenergy, 2023)
Abstract In the process of bioethanol production, more stable and active cellulase in high temperature condition is required. In this study, syringic acid was applied in cellulase hydrolysis system. At 70°C, TvEG3 activity increased 201.36%, CtBglA activity decreased 72.79% by syringic acid. With syringic acid assisting, TvEG3 thermostability was improved, CtBglA thermostability was reduced. Syringic acid scarcely affected CtCBH. In hydrolysis system with the cellulases containing TvEG3, CtCBH, and CtBglA, the reducing sugar yield improved by 28.37% with syringic acid assisting. With the molecular dynamic simulation in syringic acid system, the backbone root‐mean‐square deviation (RMSD) and the residue root‐mean‐square fluctuation (RMSF) of TvEG3, CtCBH reduced, while the RMSD and RMSF of CtBglA increased. The reduction in the number of secondary structures, especially α‐helix, caused the structure of CtBglA in the presence of syringic acid to collapse at high temperature. More secondary structures in TvEG3 and more α‐helix in CtCBH in the presence of syringic acid make them more stable at high temperatures. These means syringic acid can stabilize TvEG3 and CtCBH structure, destabilize CtBglA structure at high temperature. In summary, this study not only provides insight into cellulase hydrolysis at high temperature with syringic acid assisting but also demonstrates the promoting mechanism of syringic acid.